Deleuze, Expérimenteur (Tábano, 2025)
This essay, presented at the SPEP 2024 conference in Rochester, NY (USA), complements Alan Schrift’s talk on “Deleuze Universitaire” (linking Deleuze’s books to topics in courses he taught and especially to annual subjects required for preparing the French national agrégation examination) by studying the experimental side of Deleuze’s teaching in the deliberately experimental university, Vincennes, created in 1968-69. Given the importance of Vincennes itself as an educational experiment, Deleuze’s teaching there develops a particular kind of pedagogy that I trace, both while at Vincennes (until 1980), then at St. Denis-Paris 8 up to his retirement (1987). Finally, I consider how the work he pursued in these seminars constitutes the bases for several project in the “beyond” of Deleuze’s retirement.
Keywords: Vincennes; Deleuze; Experimental pedagogy; Deleuze’s seminars